Oil Cities Company and the Narrative of Development and Conflict (Study of Abadan Experience) - iman mombeni; Abdolhossein Kalantari; Seyyed Mohamad Ali Tavakol kosari (توسعه اجتماعی, 2020)
The city has long been a strategic site for the exploration of many major subjects such as social relations, socio-political conflicts, social order, class and power. This places cities at the heart of sociology. A space capable of producing and accumulating wealth, power, architecture, memory, collective identity and symbolic systems. The city of Abadan in the last decade of the thirteenth century (1910) until 1977 and to this day has been a city built by oil capitalism which makes it a site for urban development and conflict and this leads to form a variety of socio-urban phenomena. In this study, multiple methods and techniques includes field observation, assessing documents and historical sources, in-depth interviews, and oral history were used to study the development and conflict of the city. The results show that Abadan has been both an experience of socio-cultural development as well as an experience of conflict, duality, domination, hierarchy, and class relations. In the periods of 1912 to 1932, 1932 to 1952, and the early of 1952s to 1979, the process of development and conflict has changed, but the main trend has been to increase development and decrease conflict. Especially in the 1962s and 1972s, the idea of a developed Abadan that emerged during the nationalization of the oil industry sustained the development rather than conflict, but in general, both of these narratives have been formed together and under the influence of the oil industry.